1998
DOI: 10.1007/s004670050456
|View full text |Cite
|
Sign up to set email alerts
|

Successful renal transplantation in Jeune syndrome type 2

Abstract: Jeune syndrome (asphyxiating thoracic dystrophy) is a rare inherited disease which is fatal in early childhood in 70% of cases. Severe renal involvement may occur and lead to chronic renal insufficiency in patients who survive respiratory failure. Therefore the opportunity to perform kidney transplantation is quite rare. We report a successful cadaver renal transplantation in a 10-year-old boy with Jeune syndrome type 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Renal findings of hypertension in 2nd-3rd year of life, renal cysts (which may progress to tubular atrophy), and renal failure occurring in infancy, adolescence, or second decade of life are reported [Oberklaid et al, 1977], none of which were found in these eight cases. Renal failure occurred in 38% of those with kidney involvement [Oberklaid et al, 1977;Shah, 1980;Ring et al, 1990;Amirou et al, 1998;Tuysuz et al, 2009;De Vries et al, 2010]. The predominant cause of death for patients aged 3-10 years is renal in origin.…”
Section: Discussionmentioning
confidence: 95%
“…Renal findings of hypertension in 2nd-3rd year of life, renal cysts (which may progress to tubular atrophy), and renal failure occurring in infancy, adolescence, or second decade of life are reported [Oberklaid et al, 1977], none of which were found in these eight cases. Renal failure occurred in 38% of those with kidney involvement [Oberklaid et al, 1977;Shah, 1980;Ring et al, 1990;Amirou et al, 1998;Tuysuz et al, 2009;De Vries et al, 2010]. The predominant cause of death for patients aged 3-10 years is renal in origin.…”
Section: Discussionmentioning
confidence: 95%
“…Mortality depends on cystic changes and diffuses interstitial fibrosis (13)(14)(15)(16)(17). Abdominal USG examination of our case reported bilateral small kidneys and pelvi-caliectasis of left kidney.…”
Section: Discussionmentioning
confidence: 77%
“…Skeletal Defects NPHP can be associated with skeletal defects, including Jeune syndrome (asphyxiating thoracic dysplasia) [119][120][121][122], Ellis van Creveld syndrome [123], RHYNS syndrome (retinitis pigmentosa, hypopituitarism, NPHP, skeletal dysplasia) [124], Meckel-Gruber syndrome [115,116], and Sensenbrenner syndrome (cranioectodermal dysplasia) [125,126]. This strongly suggests a role of primary cilia function in skeletal development.…”
Section: Cardiac Defects and Situs Inversusmentioning
confidence: 98%